Repercusión del uso de facebook relacionado al destino turístico trujillo en los visitantes sociales - Altamirano Ruiz, Danny Iván (2015)
This report thesis is aimed at determining the impact of the use of social network Facebook related to tourist destination Trujillo in domestic visitors. Facebook is a new communication model, with a number of tools to capture the public; in the tourist destination Trujillo, organizations that disseminate this space, are in the virtual platform. Therefore, finding accounts that boost tourism, there is an impact on national visitors; Thus, generating motivation travel destination in Trujillo, the impact is positive in 67%, because the accounts published images, videos, texts and attachments on the attractions and activities to be developed in each. However, the hypothesis is negative use of social network generating vulgar or everyday knowledge in the tourist destination Trujillo, as the impact is negative with 41%, and that information on tourist infrastructure and superstructure is not very often, although knowledge of the attractions and tourist facilities occurs on a large scale, the first two lower total percentage, all as part of the general culture in the process of personal development of national visitors and for subsequent assessment services offered by the destination to be visited.